The addition of residue from pruning of yerba mate (Ilex paraguariensis) in laying hens modulates fatty acid profile and incorporates chlorogenic acid in the egg - da Rosa G.* (2022)
© 2022 Elsevier LtdThis study aimed to determine whether the addition of Ilex paraguariensis residue to the basal diet of laying hens improves bird health, production, fatty acids, egg quality, and transfer of chlorogenic acids to the egg. One hundred twenty birds of the Hy-line lineage were used, divided into five groups with six replicates and four birds per replicate, as follows: T0 (control group, without IPPR supplementation), T0.5 (basal diet plus 0.5% of IPPR), T1 (basal diet plus 1% IPPR), T1.5 (basal diet plus 1.5% IPPR), and T2 (basal diet plus 2% IPPR), for two consecutive cycles of 21 days each. The productive performance of the birds, physicochemical composition of eggs, fatty acid profile, the concentration of chlorogenic acids in eggs, leukocyte count, serum biochemistry, oxidant and antioxidant status, total bacterial count in eggs, and feces were evaluated at 21 and 42 days of the experiment. The addition of IPPR to the birds' diet no-change eggs production and feed conversion. In the egg yolks of birds that consumed IPPR, there were chlorogenic acids. There was a reduction in the total bacterial count in the feces and eggshells of the birds that received 2% of the IPPR. IPPR intake also reflected a reduction in total saturated fatty acid levels and increased monounsaturated fatty acids. These findings suggest that IPPR is a compelling alternative for laying hens; however, its ingestion also has negative effects that are discussed in below. Chlorogenic acids in the egg are desirable, as these phenolics have nutraceutical effects in humans.